The effect of rocuronium added to lidocaine for upper limb intravenous regional anesthesia - Lapisatepun, Worawut; Bunchungmongkol, Nutchanart; Ruangtananon, Sasiya (Biomedical Sciences and Clinical Medicine, 2024)
Objective This study aimed to determine the effect of rocuronium added to lidocaine on the onset and regression time of sensory and motor block, quality of anesthesia and postoperative analgesia in upper limb IVRA. Methods Forty adult patients undergoing elective hand/forearm surgery under IVRA, according to American Society of Anesthesiologists physical status I and II, were allocated randomly into 2 groups: group I (control) received 3 mg/kg of lidocaine diluted with saline to a total volume of 40 mL and group II (rocuronium), 3 mg/kg of lidocaine plus 0.06 mg/kg of rocuronium diluted with saline to a total volume of 40 mL. The onset and regression time of sensory and motor block were recorded as well as perioperative pain scores and fentanyl requirement. Clinical side effects after tourniquet release were also noted. Results The onset time of motor block in the rocurnium group was shorter than that in the control group (2.10±1.09 vs 26.00±8.20 min, p<0.001), while the regression time was longer in the former (25.50±10.37 vs 2.20±1.19 min, p<0.001). The quality of all anesthesia was excellent in the rocuronium group with no fentanyl requirement. However, postoperative fentanyl requirements were comparable between the two groups. Conclusion The addition of rocuronium to lidocaine in upper limb IVRA shortened the onset time of motor block and improved overall quality of anesthesia without significant side effects.